Efficacy and safety of pembrolizumab on cervical cancer: A systematic review and single-arm meta-analysis - Qi, Lin; Li, Ning; Lin, Aimin; Wang, Xiuli; Cong, Jianglin (Frontiers in Oncology, 2022)
Background: According to current research, the objective response rate and overall survival of pembrolizumab in the treatment of several types of solid tumors have been significantly improved. Some high-quality clinical trials have studied the effect of applying pembrolizumab in treating cervical cancer. Multiple clinical trials have been conducted, and some of them have shown good results as expected. Therefore, we performed this meta-analysis on existing studies to reveal the efficacy and safety of pembrolizumab in treating cervical cancer. Methods: PubMed, Embase, Cochrane Library and Web of Science were searched for literatures published until October 31, 2021. Outcomes included complete response (CR), partial response (PR), stable disease (SD), disease progression (PD), objective response rate (ORR), disease control rate (DCR), overall survival (OS), progression-free survival (PFS), the best time to response (TTR), death rate, adverse events (AE). Results: A total of 7 studies with 727 patients were included. The results were as follows: CR (0.027, 95%CI: 0.008-0.053), PR (0.104, 95% CI: 0.074-0.145), SD (0.190, 95% CI: 0.149-0.240), PD (0.541, 95% CI: 0.421-0.661). ORR was 0.155 (95% CI: 0.098-0.236) and DCR was 0.331 (95% CI: 0.277-0.385). OS was 10.23 months (95% CI: 8.96-11.50) and PFS was 4.27 months (95% CI: 1.57-6.96). TTR was 2.10 months (95%CI: 1.69-2.51). The 1-year death rate was 0.388 (95% CI: 0.230-0.574). Main adverse events included abnormal liver function, hypothyroidism, neutropenia, anemia, decreased appetite, fatigue, fever, etc. The total incidence of the adverse events of grade 3 and above was 0.212 (95% CI: 0.065-0.509). Conclusions: Pembrolizumab provides significant benefits in response rate and survival for cervical cancer patients. The results from recent high-quality clinical trials are expected to validate these findings.